Examining Chinese postgraduate students' academic adjustment in the UK higher education sector: a process-based stage model. Issue 3 (2nd April 2016) - Quan, Rose; He, Xinming; Sloan, Diane
ABSTRACT: The current theories relating to international student transition have largely tended to concentrate on what is to be adapted. This research contributes to the pedagogic literature examining how the transition is made by international postgraduate students. Using data from 20 qualitative in-depth interviews in conjunction with observations of teaching sessions and the researchers' field notes, we discovered a process-based stage model which identifies a step-by-step approach at a micro-level of academic transition. Our findings extended the prior stage modes to incorporate students' pre-arrival experience and claim that the pre-departure stage plays a crucial role on Chinese students' later academic adjustment in the UK. The finding of our four-stage-model helps not only higher education institutions increasing sensitivity to the design of study programmes and induction provision but provides practical implications for recruitment agents that attempt to engage students' pre-arrival preparations in terms of enhancing their marketing strategy in the long term.